Modeling the growth dynamics of water lettuce, Pistia stratiotes L. in wastewater - Milićević, Dragan B. (Archives of Biological Sciences, 2023)
Paper description: Growth dynamics of water lettuce under conditions of temperate-continental climate were determined. Wet biomass of the plants was measured, statistical analysis of the obtained data was performed and growth dynamics and parameters of the growth dynamics model were defined. A sigmoidal model is recommended for modeling the growth dynamics of water lettuce biomass. Based on this model the growth phases of water lettuce and the amount of biomass in individual phases were delineated. The results assist in planning preventive measures to control the spread of water lettuce, an invasive plant, and minimize negative impact on water bodies. Abstract: This study was aimed at assessing water lettuce (Pistia stratiotes L.) biomass growth, which was tested at the Faculty of Civil Engineering and Architecture of Niš under partially controlled conditions during a 70-day-long test, with a mixture of communal wastewater and water from the shaft at the hydraulic engineering demonstration facility as a source of nutrient matter. The biomass measured after the 70-day experiment ranged from 4.31 to 4.71 kg WW/m2 (average 4.48 kg WW/m2). The daily absolute growth rate (AGR) was 58.81 g/m2 day, the daily increase rate (DIR) was 16.16 %/day, the average daily relative growth rate (RGR) was 0.0359 g/g day, and the biomass doubling time (DT) was 32.94 days. The following models were used to model the dynamics of water lettuce biomass growth: the exponential model (average MSE 0.0485, average coefficient of determination (R2) to 0.9757); the logistic model (mean squared error (MSE) 0.0049, R2 0.9976), and the sigmoidal model (average MSE 0.0003, average R2 0.9999). All models have a high accuracy; however, the exponential models give a continuous increase in biomass over time, practically to infinity, without taking into account that under conditions of increased plant density and reduced availability of resources, biomass growth slows down and, therefore, they are not suitable for application in real conditions. The logistic model (environmental capacity 6.1680 kg/m2 after about 150 days, ti 53.8587 days, ta 32.8295 days, tb 74.8879), and sigmoidal model (environmental capacity 5.2903 kg/m2 after about 150 days, ti 50.2972 days, ta 34.3072 days, tb 66.2872 days) adequately describe the biomass growth of the growth phase of water lettuce with high precision, which is essential for planning appropriate preventive and active measures to control the spread of water lettuce as an invasive plant and minimize negative impacts on waterbodies in Serbia.